Pengaruh Edukasi Kesehatan terhadap Tingkat Pengetahuan Pencegahan Diabetes Melitus pada Siswa SMP Negeri 5 Kendari - Paridah Paridah; Ramadhan Tosepu; Nurmaladewi Nurmaladewi; Fifi Nirmala; Rizki Eka Sakti Octaviani Kohali (Lembaga Pengembangan Kinerja Dosen, 2026)
Diabetes Mellitus (DM) is one of the most prevalent non-communicable diseases worldwide, including Among the most common non-communicable diseases globally including Indonesia diabetes mellitus (DM) is The rising incidence of Diabetes Mellitus is partly driven by little awareness of the disease's risk factors and preventative actions. Adolescents are a key audience for health education since this time is so important for developing good habits. This study sought to evaluate how health education influences students' knowledge of Diabetes Mellitus prevention at SMP Negeri 5 Kendari. Using a one-group pretest-posttest method, this quantitative study adopted a pre-experimental design. On April 16, 2026, SMP Negeri 5 Kendari used total sampling to choose 33 pupils for the study. Before and following the health education program, data were gathered using a structured questionnaire administered. Descriptive statistics frequency distributions and percentages—were used to examine the data. Most respondents had a decent degree of knowledge (69.7%) before the intervention; 24.2% had a very good level of knowledge and 6.1% had a fair level of knowledge. After the health education program, the percentage of respondents with a very good level of knowledge rose to 69.7%; those with a good level of knowledge made up 30.3% and no respondents were left in the fair knowledge group. Health education successfully raised students' knowledge of diabetes Mellitus prevention. Hence, health education can be a good health promotion tool to improve teenagers' knowledge and help to support early diabetes mellitus prevention.